ANALISIS SISTEM DAN PROSEDUR PEMBERIAN KREDIT DALAM UPAYA MEMINIMALISIR KREDIT BERMASALAH PADA LEMBAGA PERKREDITAN DESA ( LPD ) DESA ADAT MANGGISSARI - Kadek Lisa; Sang Ayu Putu Arie Indraswarawati; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2022)
Credit is an activity of providing loans to parties in need, by returning interest and principal based on the agreed time. Proper system processes and procedures in providing credit will be able to reduce the occurrence of non-performing loans. This study aims to find out about the implementation of the credit system and procedures in the LPD of the Manggissari traditional village. The data collection methods used in this study were interviews and documentation, and were analyzed using qualitative descriptive analysis. The results in this study explain that the credit granting system consists of several procedures, namely credit application, data verification, credit decisions and credit realization. The documents required for granting credit are a letter of credit application, minutes of credit or loan agreements, minutes of handover of credit guarantees, prime credit notes, and BKK (Proof of Cash Out). The sections involved in granting credit are credit analysts, LPD chairman, and LPD treasurer. In resolving non-performing loans, it is carried out by replacing members of the management, extending the installment period, waiving interest rates, delaying interest payments and confiscation of collateral.